Field Test of Sticker Thickness in Kiln Drying Southern Pine - Laya Khademibami; Fatemeh Rezaei; Rubin Shmulsky; Seyed Abolghasem Fatemi (BioResources, 2024)
The effect of sticker thickness on final moisture content (MC) of southern pine lumber was investigated in this work. Three kiln charges of lumber were dried to examine the impact of sticker thickness. Sticker thicknesses were 0.75-, 1.00-, and 1.25-in. The moisture contents at different locations within the kiln pack (edge vs middle / course position) were noted. Three course positions were top 5, middle, and bottom 5 courses. Two within-pack locations were considered: outer 25% and middle 50%. Drying time decreased as sticker thickness increased from 0.75 in. to 1.00 in. Statistically significant interactions were noted for sticker thickness and course position (<0.0001) as well as location and course position (P= 0.0378); 1.25 in. thick stickers exhibited higher MC in comparison to 0.75 in. and 1.0 in. for top to bottom positions. Additionally, 1.0 in. thick stickers developed lower MC at the top and bottom. Lower MC was observed in outer relative to inner location regardless of course position. Lower MCs were observed at the top courses for both inner and outer location. The 1.25 in. thick stickers did not produce acceptably dry lumber given the production time constraint. The results suggested that 1.0 in. sticker thickness was most favorable.